THE MODIFICATION OF VOWEL SOUNDS IN CONVERSATIONAL SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of vowel modifications inconnected speech, focusing on processes like vowel reduction, elision, coalescence, glideformation, and changes between diphthongs and monophthongs. It explains how thesemodifications enhance fluency and efficiency in spoken language while preservingintelligibility. The discussion highlights the interplay between phonetics, linguistic structure, and social context, emphasizing the universality and variability of these processes acrosslanguages and dialects. The conclusions underscore the importance of understanding vowelmodifications for linguists, language learners, and anyone interested in the dynamics ofnatural speech. This resource is valuable for studying phonetics, sociolinguistics, and secondlanguage acquisition.